Peranan Manajemen Kas Terhadap Persediaan Kas - Danial, M; Yuli, Rini; Haryono, Ayu (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
Cash is one of the main resources to run a company's operations. Cash management executed properly can support the survival of a company where it can be seen from the cash supply.This research is conducted to determine how large a role ofmanaging inventory in cash management company from 2006 until 2010. And to perform inventory planning cash for 4 years later. Result of research on cash management PT. Cemani Toka can be said is not good enough and cause cash tumover is very low at PT. Cemani Toka and tend dispropotionately between the amount of cash sales. And advised to control and tighten cash flow and operating activities, focus in foreign exchange, but it also must set the standard management of cash inventory using the theory Harry G. Gutmann with a minimum cash balance 5% and maximum 10% from the current assets or the theory by Eugene F. Brigmann the optimum cash balance 1,5%from total assets. Keyword : cash turnover, the development of cash, cash flow